Model-Based Recursive Partitioning with Adjustment for Measurement Error (Applied to the Cox’s Proportional Hazards and Weibull Model) - Birke, Hanna (Springer, 2015)
This master’s thesis was written under the direction of Prof. Dr. Thomas Augustin at the Department of Statistics of the Ludwig-Maximilians-University Munich. In particular, I would like to express my gratitude to Prof. Dr. Thomas Augustin for the interesting and relevant topic of the thesis, for the good cooperation as well as for his helpful and valuable suggestions. I appreciate his support at any time. In addition, I wish to thank Teresa for proofreading my thesis and for her constructive comments. I would like to thank my ’stät girls’ Ina, Kathrin, Sonja and Teresa as well as Markus. I am grateful to have found such amazing friends who have accompanied me throughout my studies. Furthermore, I thank Jan, Michael, my sister Lena and especially my parents for their constant support and encouragement.